Natural variations at the Stay-Green gene promoter control lifespan and yield in rice cultivars - Dongjin Shin (Nature Portfolio, 2020)
Breeding crops with delayed senescence could plausibly increase grain yield. Here the authors show that variation at the rice SGR locus contributes to differences in senescence between indica and japonica subspecies and show that introgression can increase yield in an elite indica rice variety.